Cosx=1-tan^2(x/2)/1+tan^2(x/2)?

Cosx=1-tan^2(x/2)/1+tan^2(x/2)? #Cosx=(1-tan^2(x/2))/(1+tan^2(x/2))# #Cosx=(1-((1-cosx)/sinx)^2)/(1+((1-cosx)/sinx)^2)# #Cosx=(1-((1-2cosx+cos^2x)/sin^2x))/(1+((1-2cosx+cos^2x)/sin^2x))# #Cosx=(sin^2x/sin^2x-((1-2cosx+cos^2x)/sin^2x))/(sin^2x/sin^2x+((1-2cosx+cos^2x)/sin^2x))# #Cosx=((2cosx-2cos^2x)/sin^2x)/((2-2cosx)/sin^2x)# #Cosx=(cancel(2)cosxcancel((1-cosx)))/cancel(sin^2x)*cancel(sin^2x)/(cancel2cancel((1-cosx))# #cosx=cosx#

Como você encontra a derivada de #y = x ^ 2 e ^ (- x) #?

Como voc├¬ encontra a derivada de #y = x ^ 2 e ^ (- x) #? Responda: #dy/dx=xe^-x(2-x).# Explica├ž├úo: #y=x^2e^-x# #:. dy/dx=x^2*d/dx(e^-x)+e^-x*d/dxx^2#…. [Regra do produto para Diffn.] #=x^2*e^-x*d/dx(-x)+e^-x*2x#………………. [Regra da cadeia] #=-x^2e^-x+2x*e^-x=xe^-x(2-x).#